Shouldn't you be in school? - Snicket, Lemony; Seth, 1962- (New York : Little, Brown & Company, 2014)
Young Lemony Snicket investigates a rash of fires that have plagued the town of Stain'd-by-the-Sea, revealing secrets that involve the Department of Education and the notorious villain Hangfire.
English Language & Literature.
Keywords: Apprentices -- Juvenile fiction; Arson investigation -- Juvenile fiction; Detective and mystery stories; Humorous stories; Apprentices -- Fiction; Arson investigation -- Fiction; Mystery and detective stories; Humorous stories; Apprentices; Arson investigation; Fiction; Juvenile works; Mystery fiction; Humorous fiction